Innovative Strategische Umweltprüfung für die Nahverkehrsplanung. Nachhaltigkeit für den kommunalen ÖPNV. - Bongardt, Daniel; Krummheuer, Florian (Deutscher Verkehrs-Verl., 2008)
Durch die Verabschiedung der EU-Richtlinie zur Strategischen Umweltprüfung (SUP) und die Änderung des Gesetzes über die Umweltverträglichkeitsprüfung (UVPG) am 25. Juni 2005 sind viele Verkehrspläne in Deutschland prüfpflichtig geworden. Auch kommunale Nahverkehrspläne haben sich mittlerweile bei vielen Aufgabenträgern zu einem zentralen Planungsinstrument mit zunehmendem Regelungsgehalt entwickelt, so dass sie auf ihre Umweltwirkungen hin systematisch betrachtet werden sollten. Die SUP bietet sich an, da sie mit geringem Aufwand nachhaltigere ÖPNV-Planung ermöglicht. difu

Since the 1990th German municipalities need to pass local public transport plans (NVP) which give a framework for the transport companies' in-detail planning such as scheduling and run cutting. First experiences on evaluating such plans by a Strategic Environment Assessment (SEA) have been made recently in Germany. Two case-studies show that there are very different approaches to do a SEA for NVP. While in the Hanover region the authorities put their focus on the land consumption of new infrastructures the Ennepe-Ruhr-Region evaluates the plan's effects on the modal split. Both approaches focus mainly on the actual inspection of environmental impacts and less on the SEA-proceeding with its various steps. For example the definition of environmental aims was not constituted in both cases. Based on these observations the authors recommend a SEA for NVP which focuses stronger on the procedural steps of the SEA. This should lead to environmentally improved plans with very few efforts in a very transparent manner. The SEA therefore needs to be recognized as environmental audit scheme for public transport plans. difu
Innovative strategic environmental assessment for public transport plans.
Keywords: Verkehr; Umweltverträglichkeitsprüfung; ÖPNV; Nahverkehr; Personennahverkehr; Verkehrsplanung; Umweltplanung; Planungspraxis; Strategische Umweltprüfung; EG-Richtlinie; Umweltauswirkung; Nahverkehrsplanung; Fallbeispiel